Evaluation of the entrepreneurship education program through extracurricular activities of Student Company - Firmansyah Firmansyah; Wardani Rahayu; Nurjannah Nurjannah (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
The study aims to evaluate the entrepreneurship education program through extracurricular activities of Student Company at a school using a modified CIPP and Kirkpatrick evaluation model. The research found that (1) the context of the program has been very good to provide facilities to the students who want to develop their entrepreneurial potential at school. The vision, mission, and objectives of the entrepreneurship education program at the vocational high school are able to describe the future expectations for students, especially in the field of entrepreneurship. (2) The supporting program implementation factors are in the “high” category and able to support program implementation following the objectives. (3) The implementation of entrepreneurship education program through Student Company extracurricular activities is in the “middle” category, seen from some discrepancies found between the program plans and implementation. (4) The satisfaction level of students taking part in entrepreneurial education program activities is in the “middle” category, seen from their several complaints about the activities of Student Company that are not following the program plans. (5) The level of knowledge of students taking part in the Student Company extracurricular activities is in the “high” category. (6) The application of entrepreneurial values in the daily activities of students taking part in the Student Company extracurricular activities is in the “middle” category. (7) The level of self-efficacy of students towards entrepreneurship is in the “low” category. The program of entrepreneurship education through extracurricular activities of Student Company is not fully able to increase students' interest in entrepreneurship.